PENGARUH INTELLECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2020) - Lesatanova Tricahya Avilya; Imam Ghozali (Diponegoro Journal of Accounting, 2022)
This research was conducted to analyze the effect of of Intellectual Capital, Good Corporate Governance, and Corporate Social Responsibility on financial performance with earnings management as a mediating variable. Intellectual Capital, Good Corporate Governance, and Corporate Social Responsibility are independent variables. Then the dependent variable used is financial performance, and the mediating variable is earnings managementThe sample of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020 with a total of 87 companies.  The sample selection method used purposive sampling method by preparing the criteria and requirements that had been determined by the researcher.  The analytical method used in this study is the Partial Least Square methodThe results of the study show that Intellectual Capital and Corporate Social Responsibility have a positive influence on financial performance. Good Corporate Governance has no significant and positive effect on financial performance. Earnings management has a negative effect on financial performance.  In addition, there are results that show an indirect influence where earnings management is not able to mediate Good Corporate Governance and Corporate Social Responsibility on financial performance.